ANALISIS PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SINGKONG KEJU DI ARGOTELO SALATIGA - Melfa Br Sirait; Bayu Nuswantara (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
Cassava is one of the staple foods for most of the Indonesian population which is in great demand by people from various circles. Because in addition to the cheap price and the easy way to get it. The easy process of planting cassava is also one of the reasons why cassava is in great demand by the public. This study aims to determine the characteristics of respondents, make decisions and analyze consumer attitudes towards attributes. This research was conducted in Argotelo in the Salatiga area of Central Java. The type of research used is descriptive quantitative research. The sampling technique used is convenience sampling with a sample size of 40 respondents. Sources of data were obtained from interviews, questionnaires, literature study, and documentation. The data analysis techniques used are Descriptive Analysis, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The results showed that the characteristics of consumers aged 20 to 28 years were married with income below Rp. 2,500,000 as private employees and have the latest diploma or bachelor's education (S1, S2, S3). The decision-making stage is the introduction of needs, information search, evaluation of alternatives, purchase, and results. The consumer satisfaction index is 86.40%, which means that consumers are very satisfied with the cassava cheese products in Argotelo. There is no priority for performance on attributes that need to be improved, but in quadrant II the taste and quality need to be maintained and in quadrant III it needs to be encouraged or developed, especially brand attributes so that consumer expectations for the brand are higher